Documenting metrological traceability as intended by ISO 15189:2012: A consensus statement about the practice of the implementation and auditing of this norm element - Thelen,M.; Vanstapel,F.; Brguljan,P.M.; Gouget,B.; Boursier,G.; Barrett,E.; Kroupis, C.; Lohmander,M.; Sprongl,L.; Vodnik,T.; Bernabeu-Andreu,F.; Vukasovic,I.; et al. (Clin.Chem.Lab Med., 2019)
ISO15189:2012 requires medical laboratories to document metrological traceability of their results. While the ISO17511:2003 standard on metrological traceability in laboratory medicine requires the use of the highest available level in the traceability chain, it recognizes that for many measurands there is no reference above the manufacturer's selected measurement procedure and the manufacturer's working calibrator. Some immunoassays, although they intend to measure the same quantity and may even refer to the same reference material, unfortunately produce different results because of differences in analytical selectivity as manufacturers select different epitopes and antibodies for the same analyte. In other cases, the cause is the use of reference materials, which are not commutable. The uncertainty associated with the result is another important aspect in metrological traceability implementation. As the measurement uncertainty on the clinical samples is influenced by the uncertainty of all steps higher in the traceability chain, laboratories should be provided with adequate and appropriate information on the uncertainty of the value assignment to the commercial calibrators that they use. Although the between-lot variation in value assignment will manifest itself as part of the long-term imprecision as estimated by the end-user, information on worst-case to be expected lot-lot variation has to be communicated to the end-user by the IVD provider. When laboratories use ancillary equipment that potentially could have a critical contribution to the reported results, such equipment needs verification of its proper calibration and criticality to the result uncertainty could be assessed by an approach based on risk analysis, which is a key element of ISO15189:2012 anyway. This paper discusses how the requirement for metrological traceability as stated in ISO15189 should be met by the medical laboratory and how this should be assessed by accreditation bodies
IS - 1437-4331 (Electronic) IS - 1434-6621 (Linking) LA - eng PT - Journal Article SB - IM
Keywords: analysis; Calibration; Consensus; Greece; Humans; Medical Laboratory Science; Quality control; Reference Standards; Spain; Standards; uncertainty